Intermediate Stage Complex Regional Pain Syndrome Type 1 Is Unrelated to Proinflammatory Cytokines - Renate J. M. Munnikes; Christel Muis; Martine Boersma; Claudia Heijmans-Antonissen; Freek J. Zijlstra; Frank J. P. M. Huygen (Mediators of Inflammation)
The aim of this paper is to determine the involvement of tumour necrosis factor-α (TNF-α) and interleukin (IL)-6 in intermediate CRPS 1 as locally formed mediators of inflammation. In this study, 25 patients with proven CRPS 1 (Bruehl criteria) were included. All patients participated in one of our earlier studies during the acute stage of their disease. After the disease developed into an intermediate stage, both the disease activity and the profile of inflammatory mediators were reevaluated. Disease activity and impairment were determined by means of a visual analogue scale, the McGill Pain Questionnaire, the difference in volume and temperature between the involved and uninvolved extremities, and the reduction in active range of motion of the involved extremity. Suction blisters were made on the involved and uninvolved extremities for measurement of IL-6 and TNF-α. A significant improvement in signs and symptoms of impairment was found. However, the levels of IL-6 and TNF-α in blister fluid in the involved extremity versus uninvolved extremity were still significantly raised. Although signs and symptoms are significantly improved, proinflammatory cytokines are still increased in CRPS 1 affected extremities during the intermediate stage of the disease. This indicates that the initiation and sustained development of the disease are only partially affected by proinflammatory cytokines. Follow-up in the chronic stage is necessary to draw more definite conclusions about the existence of a supposed relation between clinical signs and symptoms and the level of proinflammatory cytokines.